Causes of Water Pollution and it’s effects and control (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The study focused on “Causes of Water Pollution and its Effects and Control.”  A sample is a tow sample, which is a sample collected during a specific space movement short time duration period on the effectiveness. Record samples separately at selected locations, depths, and times. The combination of depths is recorded over to inside deep on the water column specific so, either by prior determination on water-column or at a selected place also time duration on the water-column. Biochemical oxygen demand (BOD) is also measured using a pH meter. Chemicals such as sulfates, nitrates, and chlorides have been reported to cause water bodies such as lakes, rivers, and ponds to become acidic.